Implementation of Streaming Video Information Systems for Web-Based Computer Science Learning - Adnan Buyung Nasution; Ahir Yugo Nugroho; Rama Sellyna Anggriana; Ria Eka Sari; Heri Gunawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Information systems are an example of implementing the use of technology at this time where systems are built on a computerized basis so as to facilitate or simplify human work in the economic, social, political, health and even in the education sector, there are many information systems built to support educational development or more precisely in development learning, as is the case with many learning-based streaming videos or tutorials, both tutorials for soft skill development and hard skill development, but some problems can be seen from video streaming information systems that are widely spread on internet media that it is still relatively rare to get streaming videos that focus on learning in certain fields so that it is difficult to carry out self-development to concentrate on certain fields such as focusing on the field of computer science learning. Therefore, to facilitate video-based learning, researchers have developed a computer science-based video streaming information system.